A systematic method introduced a common lncRNA-miRNA-mRNA network in the different stages of prostate cancer - Vahabzadeh, Gelareh; Khalighfard, Solmaz; Alizadeh, Ali Mohammad; Yaghobinejad, Mahsa; Mardani, Mahta; Rastegar, Tayebeh; Barati, Mahmood; Roudbaraki, Morad; Esmati, Ebrahim; Babaei, Mohammad; Kazemian, Ali (Frontiers in Oncology, 2023)
Introduction: The present study aimed to investigate the interaction of the common lncRNA-miRNA-mRNA network involved in signaling pathways in different stages of prostate cancer (PCa) by using bioinformatics and experimental methods. Methods: 70 subjects included 60 PCa patients in local, locally-advanced, biochemical relapse, metastatic, and benign stages, and ten healthy subjects were entered into the current study. The mRNAs with significant expression differences were first obtained using the GEO database. The candidate hub genes were then identified by analyzing Cytohubba and MCODE software. Cytoscape, GO Term, and KEGG software determined the hub genes and critical pathways. The expression of candidate lncRNAs, miRNAs, and mRNAs was finally assessed using Real-Time PCR and ELISA techniques. Results: 4 lncRNAs, 5 miRNAs, and 15 common target genes were obtained in patients with PCa compared to the healthy group. Unlike the significant decrease in tumor suppressors, the expression levels of common onco-lncRNAs, oncomiRNAs, and oncogenes showed a considerable increase in the patients with advanced stages, biochemical relapse and metastatic, compared to the primary stages, local and locally-advanced. Moreover, their expression levels significantly rose in the high Gleason score compared to the lower one. Conclusion: Targeting common lncRNA-miRNA-mRNA networks can be a new strategy with potentially effective treatment for prostate cancer patients.